(untitled) (Acta Polytechnica CTU Proceedings, 2019)
The paper is focused on the evaluation of the effect of earthquakes on underground structures. Free-field analysis is one solution of this task common mainly in engineering tunnelling practice, but it has some rather simplified aspects (e.g. equivalent shear strain is constant). Pseudostatic finite element calculation combines free-field analysis and the advantages of a FEM model. Dynamic effects are introduced in the form of displacements prescribed along the vertical boundaries of the FEM model in a usually static manner. This approach also implies constant material parameters for the geological profile in the horizontal direction, an arbitrary geometry of excavation, soil structure interaction and description of share waves as a time-dependent 1D analysis of the so called free-field column. Moreover, there is shown an example comparing pseudo-static FEM analysis with an analytical method. Finally, the advantages of the pseudo-static FEM method are presented.